2005
DOI: 10.1242/jeb.01703
|View full text |Cite
|
Sign up to set email alerts
|

Cost of transport is increased after cold exposure inMonodelphis domestica: training for inefficiency

Abstract: control or exercise-trained animals, indicating greater oxidative capacity. Finally, we identified an uncoupling protein 3 homologue, whose gene expression was upregulated in skeletal muscle of cold-exposed Monodelphis domestica. Cold exposure provided a potent stimulus for muscle plasticity, driving a fast-to-slow transition more effectively than exercise training. However, linked to the dramatic shift in muscle properties is an equally dramatic increase in whole animal muscle energetics during locomotion, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…thereby indicating an increase in muscle energetics (Schaeffer et al 2005). The concordant upregulation of the muscle-specific UCP3 implied a molecular explanation for thermogenic processes seen in M. domestica.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…thereby indicating an increase in muscle energetics (Schaeffer et al 2005). The concordant upregulation of the muscle-specific UCP3 implied a molecular explanation for thermogenic processes seen in M. domestica.…”
Section: Introductionmentioning
confidence: 77%
“…Previously, the lack of BAT in marsupials led to suggestions of a thermogenic role for skeletal muscle (Kabat et al 2003;May 2003;Schaeffer et al 2003Schaeffer et al , 2005. The upregulation of UCP3 in Monodelphis domestica in response to cold mimics the regulation of UCPl, suggesting that UCP3 may uncouple myotubular mitochondria and produce heat, thereby compensating for the lack of BAT.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into the evolutionary causes of this observed interspecific variation in terrestrial NCOT is likely to be fruitful. Possible correlates of variation in NCOT include climate and habitat characteristics: chronic cold exposure causes an increase in NCOT in goats Capra aegagrus hircus (Schaeffer et al, 2001) and short-tailed opossums Monodelphis domestica (Schaeffer et al, 2005), and climate has repeatedly been shown to be an important correlate of variation in energetics (White et al, 2008;Speakman and Król, 2010;White and Kearney, in press); and species from open habitats have higher maximum running speeds than those from less open habitats and arboreal species (Garland et al, 1988;White et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Reversible glutathionation of UCP3 in response to ROS and redox state provides a dynamic post-translational mechanism for regulating mitochondrial uncoupling. It also provides insight into findings from several studies that show that the UCP3 level is inversely related to exercise efficiency in humans and other animals (Mogensen et al, 2006;Schaeffer et al, 2005;Schrauwen et al, 1999).…”
Section: Uncoupling Factors In Musclementioning
confidence: 94%